The impact of head teacher praise and criticism on adolescent non-cognitive skills: Evidence from China - Ye, Xiaomei; Wang, Qiran; Pan, Yiming (Frontiers in Psychology, 2023)
Introduction Although the importance of teacher feedback has been confirmed by a great number of studies, the association of head teacher praise and criticism with adolescents’ non-cognitive skills still needs more deeper and more extensive research. Therefore, how to improve the non-cognitive skills of adolescents, especially those with disadvantaged family and economic backgrounds, has become a key concern in the field of educational practice. Methods Based on CEPS data, this paper used panel regression and PSM-DID methods to analyze the impact of head teacher feedback on an adolescent’s non-cognitive skills measured by the big-five personality scale. Results It found that praise from head teachers favorably influenced adolescents’ extraversion, agreeableness, openness, and conscientiousness, yet significantly mitigates their neuroticism. Meanwhile, the effect of criticism from head teachers is bi-facial: It made a positive effect on adolescents’ extraversion and openness but impaired their conscientiousness and neuroticism. As rural adolescents notably lag in their non-cognitive skills and are much less likely to be praised by head teachers compared to their urban peers, we estimate that when rural adolescents are frequently praised by their head teachers at the same level as urban students, their gap in extraversion, agreeableness, neuroticism, openness, and conscientiousness would be narrowed by 12.51%, 16.58%, 11.35%, 14.25%, and 24.29%. This finding has significant implications for head teacher teaching and adolescent well-being. Conclusions The study examined the effects of head teacher praise and criticism on adolescent non-cognitive skills. The results showed that adolescents who were often praised by head teachers developed better non-cognitive skills. While the effect of head teacher criticism was two-sided: it enhances extraversion and openness as well as heightens neuroticism and corrupts conscientiousness. We further analyzed the urban-rural gap in non-cognitive skills and found that rural adolescents significantly lagged, and they have a lower possibility to be often praised by the head teacher, but a higher probability to be criticized. Through the PSM-DID quasi-experimental design, it was suggested that more head teacher praise can improve the non-cognitive skills among adolescents. When rural adolescents are estimated to receive the same amount of praise as urban adolescents, the disparities reduction in their non-cognitive skills can become possible. Our findings are of great significance to promote adolescent non-cognitive skills development and improve educational equity in urban and rural areas.